O ensino de matemática financeira na educação de jovens e adultos via resolução de problemas - Borges, Francicleide da Silva (2024)
Reflecting on the Teaching of Mathematics in Youth and Adult Education (EJA) involves discussing its challenges and potential. We can observe that experiences of sociocultural exclusion are closely linked to and marked by the subjects, young and adult, inserted in the school context of EJA, and that awareness of the life experiences brought by the students should guide educators and researchers in reflections directed toward teaching and learning Mathematics in EJA. This research was developed to answer the following question: How can Problem Solving facilitate the construction of concepts in Financial Mathematics, aiming to form critical, reflective, and autonomous young adults? The general objective was to investigate how Problem Solving can contribute to the teaching and learning of Financial Mathematics in a critical and reflective manner within EJA. We sought to reflect on the importance of the Teaching-Learning-Assessment Methodology of Mathematics through Problem Solving as a teaching strategy for Financial Mathematics in Youth and Adult Education. This study was developed through a qualitative approach, conducted as pedagogical research. Our research involved 16 students enrolled in Cycle VI of EJA at a state school in Paraíba. We used various data collection instruments during the development of this research, among which we highlight the use of a field diary and photographic records. Additionally, observations of dialogues between the subjects were made. From the analyses, it became evident that Problem Solving allowed a connection with the reality of the students. EJA brings together young and adult individuals with diverse life experiences, and their trajectories have been marked by processes of sociocultural exclusion. These exclusion processes have generated consequences in various aspects of these citizens' lives, including financial and economic challenges maintained by a social system that exacerbates existing inequalities.